Help [videorecording (DVD)] - Thorne, Jack; Comer, Jodie, 1993-; Graham, Stephen, 1973- (Acorn Media International, 2022)
When Sarah starts a job in a nursing home, to her surprise she is really good at it. She's a natural with the residents, and begins to form a special bond with Tony, a younger resident who has early onset dementia. The home is chronically underfunded and when the Covid pandemic hits, it suffers from understaffing, sickness and heart-breaking losses.